2022
DOI: 10.1021/acssuschemeng.2c01024
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Exsolved NiFe/(NiFe)Ox Core–Shell-Structured Nanocatalysts on Perovskite Anode with Enhanced Coking Resistance

Abstract: A solid oxide fuel cell (SOFC) anode consisting of a NiFe bimetal alloy/(NiFe)O x (NFA/NFO) core−shell-structured nanocatalyst-decorated ceramic substrate was fabricated by in situ r e d u c t i o n o f A -s i t e d e fi c i e n t c u b i c p e r o v s k i t e (Ba 0.2 Sr 0.8 ) 0.9 Ni 0.07 Fe 0.63 Mo 0.3 O 3-δ (BSNFM) in wet H 2 at 800 °C. The BSNFM-NFA/NFO ceramic anode exhibits an excellent catalytic activity toward H 2 and hydrocarbon fuels. The La 0.8 Sr 0.2 Ga 0.83 Mg 0.17 O 3-δ (LSGM) electrolyte-supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The metallic phase, which can be well identified as an Fe–Ni alloy (JCPDS 65-3244), can form a solid solution with a floating content of Fe and Ni. The metal ions may nucleate at a subnanometer size on the surface or inside the parent perovskite and then migrate to the surface. ,, The crystal structure of the RP phase Sr 3 FeMoO 7−δ consists of perovskite Sr­(Fe 0.5 Mo 0.5 )­O 3−δ layers and rock salt (SrO) layers being stacked alternately along the c -axis. , This highly organized two-dimensional intercalated structure effectively enhances its thermal stability and facilitates the rapid transmission of oxygen species. Additionally, it is found that thermodynamically stable RP structure of Sr 3 FeMoO 7−δ with nanocatalyst decoration also exhibited improved electrochemical performance .…”
Section: Resultsmentioning
confidence: 99%
“…The metallic phase, which can be well identified as an Fe–Ni alloy (JCPDS 65-3244), can form a solid solution with a floating content of Fe and Ni. The metal ions may nucleate at a subnanometer size on the surface or inside the parent perovskite and then migrate to the surface. ,, The crystal structure of the RP phase Sr 3 FeMoO 7−δ consists of perovskite Sr­(Fe 0.5 Mo 0.5 )­O 3−δ layers and rock salt (SrO) layers being stacked alternately along the c -axis. , This highly organized two-dimensional intercalated structure effectively enhances its thermal stability and facilitates the rapid transmission of oxygen species. Additionally, it is found that thermodynamically stable RP structure of Sr 3 FeMoO 7−δ with nanocatalyst decoration also exhibited improved electrochemical performance .…”
Section: Resultsmentioning
confidence: 99%
“…79,80 NiFe alloy exsolution materials also have the potential for direct hydrocarbon SOFCs. 81,82 For example, Sun et al 83 reported that NiFe alloy nanoparticles exsolved from A-sitedeficient LaSrCrO 3 perovskite systems had better coking tolerance and fuel oxidation properties than single-metal Ni or Fe exsolution catalysts.…”
Section: Exsolution Catalysts For Energy Applicationsmentioning
confidence: 99%